Diagnosing Severe Falciparum Malaria in Parasitaemic African Children: A Prospective Evaluation of Plasma PfHRP2 Measurement - Hendriksen,AM (PLOS Medicine, 2012)
Background: In African children, distinguishing severe falciparum malaria from other severe febrile illnesses with coincidentalPlasmodium falciparum parasitaemia is a major challenge. P. falciparum histidine-rich protein 2 (PfHRP2) is released by maturesequestered parasites and can be used to estimate the total parasite burden. We investigated the prognostic significance ofplasma PfHRP2 and used it to estimate the malaria-attributable fraction in African children diagnosed with severe malaria.Methods and Findings: Admission plasma PfHRP2 was measured prospectively in African children (from Mozambique, TheGambia, Kenya, Tanzania, Uganda, Rwanda, and the Democratic Republic of the Congo) aged 1 month to 15 years withsevere febrile illness and a positive P. falciparum lactate dehydrogenase (pLDH)-based rapid test in a clinical trial comparingparenteral artesunate versus quinine (the AQUAMAT trial, ISRCTN 50258054). In 3,826 severely ill children, Plasmadiumfalciparum PfHRP2 was higher in patients with coma (p = 0.0209), acidosis (p,0.0001), and severe anaemia (p,0.0001).Admission geometric mean (95%CI) plasma PfHRP2 was 1,611 (1,350–1,922) ng/mL in fatal cases (n = 381) versus 1,046 (991–1,104) ng/mL in survivors (n = 3,445, p,0.0001), without differences in parasitaemia as assessed by microscopy. There was aU-shaped association between log10 plasma PfHRP2 and risk of death. Mortality increased 20% per log10 increase in PfHRP2above 174 ng/mL (adjusted odds ratio [AOR] 1.21, 95%CI 1.05–1.39, p = 0.009). A mechanistic model assuming a PfHRP2-independent risk of death in non-malaria illness closely fitted the observed data and showed malaria-attributable mortalityless than 50% with plasma PfHRP2#174 ng/mL. The odds ratio (OR) for death in artesunate versus quinine-treated patientswas 0.61 (95%CI 0.44–0.83, p = 0.0018) in the highest PfHRP2 tertile, whereas there was no difference in the lowest tertile(OR 1.05; 95%CI 0.69–1.61; p = 0.82). A li